Design of the DRAGET Study: a multicentre controlled diagnostic study to assess the detection of acute rejection in patients with heart transplant by means of T2 quantification with MRI in comparison to myocardial biopsies. Issue 10 (29th October 2015) - Bonnemains, Laurent; Cherifi, Aboubaker; Girerd, Nicolas; Odille, Freddy; Felblinger, Jacques
Abstract : Introduction: Patients with heart transplant are screened for silent graft rejection by recurrent endomyocardial biopsies. MRI can detect the presence of oedema non-invasively by quantitatively measuring changes of the transverse relaxation time T2 in the myocardium. Several monocentric studies have shown that T2 quantification could help detect graft rejection in a less invasive way. DRAGET is a national multicentre diagnostic study designed to prove that T2 quantification by MRI can detect graft rejection. Methods and analysis: 190 patients from 10 centres will undergo T2 quantification and endomyocardial biopsy, within 24 h, 4 to 6 times during the first year after transplantation. T2 will be computed by analysing a sequence of 10 images obtained from a short-axis slice. Specific phantoms will be used to calibrate the T2 quantification on each MR scanner to cope with the different equipment (different vendors, magnetic field strength, etc). Specific pads with known T2 will also be used during each examination and provide a quality check to cope with the different experimental conditions (temperature, etc). All MRI and biopsy data will be reinterpreted in our centre and reproducibility will be assessed. The primary outcome will be sensitivity and specificity of MRI. The secondary outcomes will be (1) prognostic values of T2, (2) reproducibility of each techniques, (3) number of adverse events during each procedures and (4) confidence of the physicians in T2 . Ethics and dissemination: Ethics approval has been obtained. The new MRI method will be disseminated at a national level and its practical usefulness will be assessed in centres not familiar with MRI T2 quantification. The ultimate aim of the DRAGET project is to replace a strategy based solely on biopsy with one based on a first-line MRI (with biopsy only when needed) for a more efficient and less invasive detection of rejection. Trial registration numbers: ANSM 2014-A00848-39, NCT02261870 .